Respuesta :
Answer: y = -1, y = 6 (choice D)
===========================================================
Work Shown:
y - (6/y) = 5
y*(y - (6/y)) = y*5 <<--- see note 1 below
y^2 - 6 = 5y
y^2 - 5y - 6 = 0
(y+1)(y-6) = 0 <<--- see note 2 below
y+1 = 0 or y-6 = 0
y = -1 or y = 6 which are the two answers
note 1: I multiplied both sides by y to clear out the fraction (the LCD is y)
note 2: I factored the left side by asking myself "what two numbers multiply to -6 and add to +5?" the answer to that question is +1 and -6 which helps lead to the factorization. An alternative route instead factoring is to use the quadratic formula
===========================================================
Work Shown:
y - (6/y) = 5
y*(y - (6/y)) = y*5 <<--- see note 1 below
y^2 - 6 = 5y
y^2 - 5y - 6 = 0
(y+1)(y-6) = 0 <<--- see note 2 below
y+1 = 0 or y-6 = 0
y = -1 or y = 6 which are the two answers
note 1: I multiplied both sides by y to clear out the fraction (the LCD is y)
note 2: I factored the left side by asking myself "what two numbers multiply to -6 and add to +5?" the answer to that question is +1 and -6 which helps lead to the factorization. An alternative route instead factoring is to use the quadratic formula
the answer is y₁=-1,y₂=6
because you have to determine the defined range
and move constant to left and change its sing
because you have to determine the defined range
and move constant to left and change its sing